2002
DOI: 10.1093/clinchem/48.1.92
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Metabolites in Human Urine after Ingestion of an Arsenosugar

Abstract: Background: Arsenic-containing carbohydrates (arsenosugars) are common constituents of marine algae, including those species used as human food. The toxicology of these compounds has not been fully evaluated. Methods: Arsenic metabolites in human urine were monitored over a 4-day period after ingestion of a synthetic specimen of arsenosugar. The metabolites were determined by HPLC-inductively coupled plasma mass spectrometry, and structural assignments were confirmed with liquid chromatography-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
127
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(140 citation statements)
references
References 27 publications
12
127
1
Order By: Relevance
“…Together, their concentration was only about 5% of total As. Some researchers have reported that DMA and a number of dimethylarsenic compounds were detected in human urine after ingestion of seaweeds or AsSugs, by the HPLC-ICP-MS method 12,13,33) . In the present study, unidentified arsenic compounds included dimethylarsenic species such as metabolites of AsSugs, although their concentrations were fairly low.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Together, their concentration was only about 5% of total As. Some researchers have reported that DMA and a number of dimethylarsenic compounds were detected in human urine after ingestion of seaweeds or AsSugs, by the HPLC-ICP-MS method 12,13,33) . In the present study, unidentified arsenic compounds included dimethylarsenic species such as metabolites of AsSugs, although their concentrations were fairly low.…”
Section: Discussionmentioning
confidence: 99%
“…iAs is methylated to monomethylarsonic acid (MMA), DMA, and trimethylarsine oxide (TMAO) in mammals [9][10][11] . AsSugs are extensively metabolized to DMA 12,13) . AsBe is only minimally metabolized in mammals 11) .…”
mentioning
confidence: 99%
“…The finding in this work of DMAE and DMAP in marine biological tissues is to our knowledge the first to be reported. Several studies have reported the presence of DMAA 19,20 and DMAE [20][21][22][23] in urine samples. Both HPLC/ICPMS and HPLC/ESI-MS/MS were used for the determination.…”
Section: A Brief Review On Findings Of Dmaa and Dmae In Biological Samentioning
confidence: 99%
“…In particular, many studies have reported detecting DMA in urine after consumption of seaweed 12,13,22,23 ) . AsSugs, the majority of which become DMA, are broken down in the body and then excreted 7,[24][25][26] .L iet al 18 ) reported that iAs were detected at levels below 2% of the total arsenic in fish or shellfish samples of Chinese seafood. However, they were not detected in algae samples.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to DMA, methylated arsenics such as arsenobetaine (AsBe), arsenocholine (AsCho), and arsenosugars (AsSugs) are abundant in seafood products 1,4 ) . Although AsBe is only minimally metabolized in mammals 5) , AsCho and AsSug are extensively metabolized to AsBe and DMA 6,7) , respectively. Therefore, large amounts of AsBe and DMA and small amounts of MMA and iAs have been observed in the urine of seafood consumers without occupational iAs exposure [8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%